PENGARUH KOMPENSASI DAN KOMUNIKASI TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PABRIK PADA PT. AGRO SARIMAS INDONESIA KABUPATEN INDRAGIRI HILIR - Hairudin, Abdul (Jurnal Tepak Manajemen Bisnis, 2017)
This study aims to determine the impact of compensation and communicationon job satisfaction and performance of employees of the plant.The analytical toolis a two-stage regression with SPSS 17 for windows. The research method is descriptivequantitative. Samples are employees of the plant amounts to 126 people. Data collectiontechniques are questionnaires and interviews.Results from this research indicate that: (1)Compensation and communication together affect the job satisfaction of employees ofthe plant. (2) Compensation effect on job satisfaction of employees of the plant (3) Communicationaffect the job satisfaction of employees of the plant. (4) Job satisfaction affectthe performance of employees of the plant.Results of the research have implicationsfor compensation and communication of employees that needs to be improved in order toincrease job satisfaction and if employees satisfaction in the plant increases, the performanceof employees of the plant will also increase.